Computer-Based Programmed Instruction Did Not Improve the Knowledge Retention of Medication Instructions of Individuals With Type 2 Diabetes Mellitus. (January 2014) - Ruiz, Jorge G.; Andrade, Allen D.; Anam, Ramanakumar; Lisigurski, Miriam; Karanam, Chandana; Sharit, Joseph
Purpose: The purpose of this study was to investigate whether computer-based programmed instruction (CPI) with a dynamic avatar (DA) improves retention of medication information better than text (controls) or better than CPI with text (T-CPI), CPI with voice (V-CPI), or CPI with static avatar with text (SA-CPI). Methods: Participants with type 2 diabetes mellitus were enrolled in a randomized controlled trial comparing TDS with CPI in 4 conditions (T-CPI, V-CPI, SA-CPI, and DA-CPI). CPI sequentially delivers segmented information in text or voice followed by a multiple-choice question. Immediately after the user selects an option, CPI delivers elaborated feedback. Satisfaction was measured immediately after the interventions, and medication knowledge was measured at 2 weeks. Results: One-hundred fifty individuals (30 per group) with a mean age 62 years (standard deviation [SD] 7.99 years) participated. There were no baseline differences in race, body mass index, education, and health literacy. Medication knowledge retention at 2 weeks was not significantly different between the groups, df (4), F = 0.17, P = .95 (TDS, mean = 25.43, SD = 5.11; T-CPI, mean = 25.07, SD = 4.98; V-CPI, mean = 25.77, SD = 4.89; SA-CPI, mean = 25.83, SD = 5.31; and DA-CPI, mean = 24.93, SD = 6.25). Satisfaction scores were significantly lower for TDS, df (4), F = 3.11, P = .01. Conclusions: CPI did not improve medication knowledge retention at 2 weeks. CPI led to higher patient satisfaction compared with controls.